Comparison of SNP Genotypes Related to Proliferative Vitreoretinopathy (PVR) across Slovenian and European Subpopulations - Xhevat Lumi; Mateja M. Jelen; Daša Jevšinek Skok; Emanuela Boštjančič; Metka Ravnik-Glavač; Marko Hawlina; Damjan Glavač (Journal of Ophthalmology)
The present study investigated the distribution of genotypes within single nucleotide polymorphisms (SNPs) in genes, related to PVR pathogenesis across European subpopulations. Genotype distributions of 42 SNPs among 96 Slovenian healthy controls were investigated and compared to genotype frequencies in 503 European individuals (Ensembl database) and their subpopulations. Furthermore, a case-control status was simulated to evaluate effects of allele frequency changes on statistically significant results in gene-association studies investigating functional polymorphisms. In addition, 96 healthy controls were investigated within 4 SNPs: rs17561 (IL1A), rs2069763 (IL2), rs2229094 (LTA), and rs1800629 (TNF) in comparison to PVR patients. Significant differences (P<0.05) in distribution of genotypes among 96 Slovenian participants and a European population were found in 10 SNPs: rs3024498 (IL10), rs315952 (IL1RN), rs2256965 (LST1), rs2256974 (LST1), rs909253 (LTA), rs2857602 (LTA), rs3138045 (NFKB1A), rs3138056 (NFKB1A), rs7656613 (PDGFRA), and rs1891467 (TGFB2), which additionally showed significant differences in genotype distribution among European subpopulations. This analysis also showed statistically significant differences in genotype distributions between healthy controls and PVR patients in rs17561 of the IL1A gene (OR, 3.00; 95% CI, 0.77–11.75; P=0.036) and in rs1800629 of the TNF gene (OR, 0.48; 95% CI, 0.27–0.87; P=0.014). Furthermore, we have shown that a small change (0.02) in minor allele frequency (MAF) significantly affects the statistical p value in case-control studies. In conclusion, the study showed differences in genotype distributions in healthy populations across different European countries. Differences in distribution of genotypes may have had influenced failed replication results in previous PVR-related SNP-association studies.